Strategi Pemasaran Syariah dalam Upaya Meningkatkan Pendapatan Pengusaha Tenun di Kelurahan Ntobo - Rahmatan Setiadin; Umar Sagaf; Muhammad Zia Ulhaq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyse sharia marketing strategies in increasing the income of weaving entrepreneurs in Ntobo Village, Bima City. The traditional weaving industry in this region not only has high cultural value, but is also the main source of livelihood for the local community. However, weaving entrepreneurs face challenges in the form of limited market access, competition with imported products, and lack of understanding of sharia marketing and modern marketing strategies. This research uses a descriptive qualitative method with data collection techniques through observation, semi-structured interviews, and documentation of 15 weaving entrepreneurs. The results showed that the implementation of sharia marketing strategies, which include honesty and transparency in transactions, provision of halal and quality products, sharia value-based promotion through social media, and strengthening personal relationships with consumers, contributed positively to increasing consumer confidence and entrepreneurial income. In addition, collaboration through artisan communities and participation in exhibition activities helped expand the marketing network. Despite facing challenges in terms of capital, market access and digital skills, weaving entrepreneurs in Ntobo have great opportunities through government support and increased public awareness of local products based on Islamic values. This study concludes that the integration of sharia principles and modern marketing strategies can sustainably increase the competitiveness and income of weaving entrepreneurs, while maintaining the cultural and religious values of the Ntobo community.